Large‐scale functional brain connectivity during emotional engagement as revealed by beta‐series correlation analysis. (25th July 2016) - Kang, Daesung; Liu, Yuelu; Miskovic, Vladimir; Keil, Andreas; Ding, Mingzhou
Abstract: It has been hypothesized that the medial prefrontal cortex (mPFC) is a hub in the network that mediates appetitive responses whereas the amygdala is thought to mediate both aversive and appetitive processing. Both structures may facilitate adaptive responses to emotional challenge by linking perception, attention, memory, and motor circuits. We provide an initial exploration of these hypotheses by recording simultaneous EEG‐fMRI in eleven participants viewing affective pictures. MPFC‐ and amygdala‐seeded functional connectivity maps were generated by applying the beta‐series correlation method. The mPFC‐seeded correlation map encompassed visual regions, sensorimotor areas, prefrontal cortex, and medial temporal lobe structures, exclusively for pleasant content. For the amygdala‐seeded correlation map, a similar set of distributed brain areas appeared in the unpleasant‐neutral contrast, with the addition of structures such as the insula and thalamus. A substantially sparser network was recruited for the pleasant‐neutral contrast. Using the late positive potential (LPP) to index the intensity of emotional engagement, functional connectivity was found to be stronger in trials with larger LPP. These results demonstrate that mPFC‐mediated functional interactions are engaged specifically during appetitive processing, whereas the amygdala is coupled to distinct sets of brain regions during both aversive and appetitive processing. The strength of these interactions varies as a function of the intensity of emotional engagement.